APPLICATION OF CRIMINAL RESPONSIBILITY LAWS FOR OFFENDERS PARTICIPATING IN NARCOTICS ABUSE - Pudjawijaya, IGM Seli; Pratiwi, Siswantari; Mardani (International Peneliti Ekonomi, Sosial dan Teknologi, 2024)
The consequences caused by narcotics abuse are very detrimental to the continuity of life of the younger generation as the majority, which ultimately impoverishes a country because it does not have a quality next generation to replace the generation that has entered retirement age. The problem is : How is the application of the law on criminal liability for perpetrators who participate in narcotics abuse (Case Study of Decision Number 46/Pid.Sus/2017/PN Mln and Decision Number 89/Pid.B/2015/PN Mam ? How do judges consider decisions regarding perpetrators who participate? narcotics abuse (Decision Number 46/Pid.Sus/2017/PN Mln and Decision Number 89/Pid.B/2015/PN Mam )? The research method used is normative legal research. The conclusion is that participating in Indonesian narcotics criminal law is an act that can be punished as considered by the panel of judges in decision Number 46/Pid.Sus/2017/PN Mln and Decision Number 89/Pid.B/2015/PN Mam and the basis for the judge's consideration is that it can be analyzed, namely considering all aspects related to the main case that occurred and then looking for statutory regulations that are relevant to the main disputed case as a legal basis. in rendering a decision.